2020
DOI: 10.33160/yam.2020.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring of Home Oxygen Therapy: A Review of the State of the Art and Introduction of a New Cloud-based System

Abstract: Home oxygen therapy allows patients requiring longterm oxygen therapy to receive care at home and helps improve the prognosis of patients with chronic respiratory failure. The usage conditions of oxygen concentrators, which are used to supply gaseous oxygen, and the effects of oxygen inhaled at a prescribed flow rate have not been confirmed in adequate detail. As a result of advances in information and communications technology, internet communication functions can now be incorporated into medical devices inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It records the usage of oxygen concentrator and accessed remotely by health care supplier. The use of tele-monitoring system for home oxygen therapy with the cloud-based analytical system developed in Japan, recently reported by Naoto Buriok (2020) [19] which recognized as a new medical technology.…”
Section: Recent Development On Oxygen Concentratormentioning
confidence: 99%
“…It records the usage of oxygen concentrator and accessed remotely by health care supplier. The use of tele-monitoring system for home oxygen therapy with the cloud-based analytical system developed in Japan, recently reported by Naoto Buriok (2020) [19] which recognized as a new medical technology.…”
Section: Recent Development On Oxygen Concentratormentioning
confidence: 99%
“…Telemonitoring data of the devices delivering oxygen such as oxygen concentrators or portable carriers, and of patients' physiological and clinical conditions can be stored on a server and accessed remotely by health care providers on demand, enabling them to check the performance of and the compliance to LTOT and, in the case of need, to intervene appropriately. In countries such as Japan, LTOT telemonitoring is covered by social insurance systems and is recognised as a new medical technology [24].…”
Section: Long-term Oxygen Therapymentioning
confidence: 99%
“…1,2 Chronic obstructive pulmonary disease (COPD), which is the leading cause of chronic respiratory failure in Japan, is known to have negative effects on the autonomic nervous system. 3 The clinical condition of patients with COPD is monitored by assessing percutaneous arterial blood oxygen saturation (SpO 2 ) with a pulse oximeter, 4,5 which can be used to also measure pulse rate variability (PRV) through the photoplethysmography method. 6 It has been reported that autonomic nervous system function can be analyzed by measuring PRV with a pulse oximeter instead of HRV, which appears satisfactory in healthy subjects at rest.…”
mentioning
confidence: 99%